EFEKTIVITAS FUNGI CIPANAS DALAM BIOKONVERSI TANDAN KOSONG KELAPA SAWIT (TKKS) MENJADI PULP KERTAS KORAN - Ridwan Achmad Pasaribu; Setyani Budi Lestari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Empty oil-palm bunches (EOPB), due to high contents of lignin (24.68 percent) and extractives (5.57 percent), is less economical when it is pulped using the conventional semi-chemical or semi- mechanical process into newsprint pulp. The conventional process is unable to partly dissolve the lignin and ex/ractives effectively, and consequently produces EOPB pulp with undesirable results, i.e. low screened yield, poor qualities, and longer defiberation and fibrillation duration. As one way to cope with it, the EOPB prior to the soda anthraquinone (AQ) semi-chemical pulping should be pretreated by biodelignification.In this regard, the EOPB chips were biodelignified through the inoculation of the raw materials with the Cipanas-strainfungi (CPSOI) as much as 5-and 10-percent (oven dry weight), and further incubated for I0-and 20-days. Afterwards, the fungi-treatedchips were semi-chemically pulped using the soda-AQ process into newsprint pulp after they are cooked in an electrically heated digester. After the cooking, the EOPB chips were defiberized in a Hollander beater, stone-refined, and then fibrillated in a Niagara beater into ultimately the EOPB pulp with the degree offreeness at 300 CSF. The handsheet was further prepared from the EOPB pulp with the basis weight 45 - 50 gram per m3. This experiment was mainly aimed at evaluating the effectiveness of biodelignification using Cipanas-strain fungi on the chemical components, processing properties, and qualities of the resulting EOPB pulp for newsprint. The chemical analysis revealed that the inoculation of the EOPB chips with 10-percent of CPSO I isolat followed by 20-day incubation period brought about the decreases in lignin and extractive contents by 6.32-and-2.61-percent, respectively. Besides such biodelignification also induces the increase in pulp yield (by maximally 3.98 percent), and the decreases in kappa number and energy consumption (by 11.19 and 17.56 percent, respectively). Further, the EOPB 's pulp handsheet for newsprint achieved particular values of tensile index (43.67 Nm/gr), tear index (7.96 Nm2/kg), opacity (93.98 percent) and brightness (58.04 °GE) which corresponded to those of Indonesian National Standard (SNI) No.14-0691-1998 for newsprint.